Mastering Microsoft Teams end user guide to practical usage, collaboration, and governance - Hubbard, Melissa; Bailey, Matthew J. (Apress, 2018)
Do you need to learn how to use Microsoft Teams? Are you questioning how to drive user adoption, govern content, and manage access for your Teams deployment? Either way, Mastering Microsoft Teams is your one-stop-shop to learning everything you need to know to find success with Microsoft Teams. Microsoft's new chat-based collaboration software has many rich features that enable teams to be more efficient, and save valuable time and resources. However, as with all software, there is a learning curve and pitfalls that should be avoided. Begin by learning the core components and use cases for Teams. From there the authors guide you through ideas to create governance and adoption plans that make sense for your organization or customer. Wrap up with an understanding of features and services in progress, and a road map to the future of the product. What You'll Learn: Implement, use, and manage Microsoft Teams Understand how Teams drives productivity and engagement by combining the functionality of Microsoft Groups, SharePoint, OneDrive, Outlook, and other services in one location Govern, explain, and use Teams in your organization Know the pitfalls to avoid that may create challenges in your usage of Teams Become familiar with the functionality and components of Teams via walkthroughs, including opportunities for automating business processes in Teams This book is for anyone who wants to learn Microsoft Teams. To get the most out of the book, a basic understanding of Office 365 and a subscription, including a Microsoft Teams license, is useful. Melissa Hubbard is a Microsoft MVP and an Office 365 and SharePoint consultant specializing in collaboration solutions and automating business processes. She is a certified Project Management Professional (PMP) experienced in project management and quality assurance as well as implementing SharePoint and Office 365 solutions. She is passionate about user adoption, governance, and training. Melissa regularly blogs and speaks at events and conferences, most recently on the topics of Microsoft Teams and Flow. Matthew J. Bailey is a Microsoft MVP and Microsoft Certified Trainer (MCT) for Noteworthy Technology Training, specializing in SharePoint, Office 365 (including Teams), Azure, and Power BI. He combines his business expertise and his technical knowledge to resolve corporate challenges. He is a highly regarded presenter, avid blogger, and author, most recently of The SharePoint Business Analyst Guide.
Includes index. - Online resource; title from PDF title page (EBSCO, viewed August 23, 2018)
Keywords: Microsoft Team manager; Microsoft Office; Business mathematics & systems; Microsoft programming; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior